2008
DOI: 10.1007/s11240-008-9371-3
|View full text |Cite
|
Sign up to set email alerts
|

Maturation of somatic embryos in two embryogenic cultures of Picea morrisonicola Hayata as affected by alternation of endogenous IAA content

Abstract: Embryogenic culture lines T4 and T2 were initiated from two mature zygotic embryos of Picea morrisonicola Hay. Mature somatic embryos (SEs) were produced in culture line T2 but not in line T4 after 8-week abscisic acid (ABA) treatment. High performance liquid chromatography (HPLC) analysis of the endogenous indole-3-acetic acid (IAA) content has shown 7.5 times higher IAA production in T4 line than in T2 line during the proliferation phase. However, after ABA incubation the line T4 produced much less IAA than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 46 publications
1
14
1
2
Order By: Relevance
“…The effect of lower concentrations was less dramatic but a stimulating effect of PCIB on the development of somatic embryos was not found in the concentration range used. Our results are contrary to those of Find et al [46] and Liao et al [44] who obtained an increase in the yield and quality of somatic embryos of Abies nordmanniana and Picea morrisonicola by exogenous treatments with several auxin antagonists, including PCIB. They suggested that the effects of endogenously produced auxin may be one reason for low or failing maturation of embryogenic cultures.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The effect of lower concentrations was less dramatic but a stimulating effect of PCIB on the development of somatic embryos was not found in the concentration range used. Our results are contrary to those of Find et al [46] and Liao et al [44] who obtained an increase in the yield and quality of somatic embryos of Abies nordmanniana and Picea morrisonicola by exogenous treatments with several auxin antagonists, including PCIB. They suggested that the effects of endogenously produced auxin may be one reason for low or failing maturation of embryogenic cultures.…”
Section: Discussioncontrasting
confidence: 99%
“…PCIB was also used successfully to inhibit auxin action in the ESM of fir [46] and was found to retard proliferation and promote the development of numerous high-quality mature embryos of Abies nordmanniana [46]. PCIB used in Picea morrisonicola proliferation increased embryo production in embryogenic culture with high auxin production [44]. The effect of PCIB on the maturation of Abies alba ESM in this study is strongly dependent on the concentration used.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…The anti-auxin transport inhibitor TIBA and the growth retardant DM have been utilized in plant tissue culture to adjust the endogenous hormonal balance of in vitro cultured explants, in order to induce a specific differentiation in tissues (Lall et al, 2005;Liao et al, 2008;Kepenek and Karoğlu, 2011). This was supported in the current study by the formation of adventitious shoots and roots in response to TIBA and DM but not cytokinins.…”
Section: Effects Of Growth Regulators On In Vitro Morphogenesismentioning
confidence: 99%